Principles and applications of molecular diagnostics - Rifai, Nader; Horvath, Andrea R.; Wittwer, C.
Principles and Aspects of Molecular Diagnostics is an accessible guide for clinical chemists and biologists applying molecular technology to clinical diagnosis. The book consists of two parts, with Part One covering principles and analytical concepts in molecular diagnostics, such as genomes and variants, nucleic acids isolation and techniques, circulating tumor cells and DNA, and cellular DNA. Part Two presents clinical applications of molecular diagnostics in solid tumors, prenatal diagnosis, infectious disease, genetic disease, hematopoietic malignancies, pharmacogenetics and identity testing. This book is ideal for those who need a thorough, yet succinct, guide on the use of this technology for molecular testing. Explains the principles and tools of molecular biology, along with the modern analytical tools that can be used to obtain the best results.